Novel no‐stop FLNA mutation causes multi‐organ involvement in males. Issue 9 (19th July 2013) - Oegema, Renske; Hulst, Jessie M.; Theuns‐Valks, Sabine D.M.; van Unen, Leontine M.A.; Schot, Rachel; Mancini, Grazia M.S.; Schipper, Marguerite E.I.; de Wit, Marie C.Y.; Sibbles, Barbara J.; de Coo, Irenaeus F.M.; Nanninga, Veerle; Hofstra, Robert M.W.; et al.
ABSTRACT Mutations in FLNA (Filamin A, OMIM 300017) cause X‐linked periventricular nodular heterotopia (XL‐PNH). XL‐PNH‐associated mutations are considered lethal in hemizygous males. However, a few males with unusual mutations (including distal truncating and hypomorphic missense mutations), and somatic mosaicism have been reported to survive past infancy. Two brothers had an atypical presentation with failure to thrive and distinct facial appearance including hypertelorism. Evaluations of these brothers and their affected cousin showed systemic involvement including severe intestinal malfunction, malrotation, congenital short bowel, PNH, pyloric stenosis, wandering spleen, patent ductus arteriosus, atrial septal defect, inguinal hernia, and vesicoureteral reflux. The unanticipated finding of PNH led to FLNA testing and subsequent identification of a novel no‐stop FLNA mutation (c.7941_7942delCT, p.(*2648Serext*100)). Western blotting and qRT‐PCR of patients' fibroblasts showed diminished levels of protein and mRNA. This FLNA mutation, the most distal reported so far, causes in females classical XL‐PNH, but in males an unusual, multi‐organ phenotype, providing a unique insight into the FLNA‐associated phenotypes. © 2013 Wiley Periodicals, Inc.